The Relationship Between Physical Exercise and Mobile Phone Addiction Tendency of University Students in China: A Moderated Mediation Model - Guo, Ke-lei; Ma, Qi-shuai; Yao, Shu-jun; Liu, Chao; Hui, Zhen; Jiang, Juan; Lin, Xi (Frontiers in Psychology, 2022)
This study aims to explore the relationship between physical exercise(PE), self-control(SC), physical exercise atmosphere(PEA)and mobile phone addiction tendency(MPAT) among Chinese university students. Through the quota sampling, 1433 students complied with the requirements were surveyed from 10 universities in China.PE, SC, PEA and MPAT were assessed using standard scales. For data analysis, common method deviation test, mean number, standard deviation, correlation analysis and structural equation model analysis were carried out in turn. The results showed PE and MPAT were negatively related(r=–0.158,p＜0.05); PE significantly positively predicted SC(β=0.082, t=3.748, P<0.01), and SC significantly negatively predicted MPAT (β=–0.743, t=–19.929, P<0.01). Bootstrap method was used to test the mediating effect of SC. The results showed that 95% confidence interval did not include 0. After adding the mediating variable of SC, PE did not significantly negatively predict the tendency of MPAT(β=– 0.027, t=–1.257, p＞0.05). The interaction item PEA and SC could significantly positively predict the tendency of MPAT(β=0.165, t=2.545, p＜0.05). In the high PEA group, SC had a significant negative predictive effect on the tendency of MPAT(β=–0.665, t=–14.408, p＜0.01); However, in the low PEA group, the negative predictive effect was stronger(β=–0.834, t=–15.015, p＜0.01). The present study shows that PE significantly negatively predicted the tendency of MPAT, and SC played a complete mediating role in the relationship between PE and MPAT; The second half of the indirect effect of PE and MPAT was regulated by the PEA. The PEA will enhance the influence of SC on MPAT, but the high PEA will increase the level of MPAT of individuals at a very high level of SC.